Pengembangan E-LKPD Berbasis HOTS Untuk Meningkatkan Kemampuan Berpikir Kritis Dalam Pembelajaran IPS di Sekolah Dasar - Yulita; Rahman Hakim, Zerri; Sari Dewi, Ratna (Papanda Publisher, 2025)
Critical thinking skills are essential for 21st-century education, yet their development in elementary schools remains suboptimal due to limited engaging and accessible learning materials. Objective: This study aimed to develop and validate a HOTS-based E-LKPD (Electronic Student Worksheet) to enhance critical thinking skills in social studies learning for fifth-grade elementary students. Methods: This research employed a Research and Development (R&D) method following Borg and Gall's modified model through six stages: problem analysis, data collection, product design, validation, revision, and limited trial. Validation involved six experts (material, media, and language), while the trial included 15 fifth-grade students at SDN Pasilian III using pre-test and post-test designs. Results: Expert validation yielded an average feasibility score of 86.9% (very feasible category), with material experts scoring 82.8%, language experts 88.1%, and media experts 89.9%. The implementation showed significant improvement in students' critical thinking skills, with mean scores increasing from 40.8 (pre-test) to 83.7 (post-test), achieving an N-Gain of 0.66 (moderate category). Conclusion: The HOTS-based E-LKPD is feasible and effective for enhancing elementary students' critical thinking skills in social studies learning, providing a practical solution for implementing HOTS-based instruction in elementary schools.